ACCOUNTING TRACTION POWER SUPPLY SYSTEM RELIABILITY DURING REGULATION OF THEIR REGIMES - Кузнецов, Валерий Геннадиевич (Eastern-European Journal of Enterprise Technologies, 2012)
This article offered the methological approache to the accounting the reliability of regulation devices of DC traction power supply systems during regulation of their regimes.